Case in point: skating into sports medicine - Kirillov, E.; Smith, M.; Driban, J. B. (International Journal of Athletic Therapy & Training, 2023)
A few years ago, we offered a roadmap to bridge the gap between athletic training researchers and clinicians to optimize athlete safety and clinical management.1 However, it is crucial to recognize that other stakeholders belong at the table (e.g., patients, public, parents, payers/insurers, policymakers, product makers). Perhaps, most importantly, we must give our patients/athletes a seat at the table. While we strive for our patients to engage in shared decision making, they should also have an opportunity to inform clinicians and researchers on their perceptions about how the sports medicine team could better address their needs. In our "Case in Point" article, we provide a chance for an ice skater, who is a member of the Haydenettes synchronized skating team, to identify the needs within her community and a chance for solutions. As a member of the Haydenettes, she is the 2022 and 2023 U.S. Synchronized Skating Champion, and 2022 and 2023 World Synchronized Skating Competitor. The skater has also represented the United States at the 2018 and 2019 World Synchronized Skating Championships, and the 2015, 2016, and 2017 Junior World Synchronized Skating Championships. In the second section, a clinician who works with skaters provides their perspective on the skater`s call to action. Finally, in the third section, a researcher shares suggestions based on the views of the skater and clinician. Each stakeholder had a chance to see the complete draft and provide feedback to each other. We hope this "Case in Point" article highlights how novel clinical and research ideas can be sparked by creating a forum for athletes/patients, providers, and researchers to share ideas.